Accuracy of Analysts' Earnings Forecasts: Evidence from Mergers and Acquisitions in Australia - Janice C. Y. How; Yion K. Phung (Asian Academy of Management Journal of Accounting and Finance, 2005)
As the incidence of mergers and acquisitions (M&As) continues to escalate, understanding the factors that systematically affect earnings predictability becomes increasingly important. This paper examines how changes in business characteristics and forecasting environment of merging firms affect the accuracy of consensus analysts' earnings forecasts in Australia. Based on a sample of 99 M&As from 1998 to 2000, the results show that the forecast error increases after an M&A. The increase in the forecast error appears to persist for at least the first three years after the merger, suggesting that analysts take time to adjust to changes in the firm brought about by an M&A. The change in analysts' forecast errors is related to variables proxying the change in the complexity of the merging firms.